Perancangan Sistem Informasi Kelengkapan Pengisian Resume Medis Rawat Jalan di Rumah Sakit - Nurafni Hanifah; Sabila Aulia Reihan; Yuda Syahidin; Meira Hidayati (Universitas Bandar Lampung (UBL), 2021)
Hospital is an establishment that's engaged within the field of health service institutions that provide perfect health services for every individual who organizes outpatient, inpatient, and emergency services. By providing health services, hospitals must have complete data from patients in order that services get optimal results. At the time of service, the medical history department is that the most vital role. additionally, to provide services together with it, the medical history section also processes historical data from the patient. This medical record consists of registration, filling inpatient data, processing, data analysis, and documentation. If the medical record sheet is filled out completely and properly, the health history is going to be said to be appropriate and good. the tactic administered through chemical analysis resulted in the conclusion that the outpatient medical resume form in 2019 at the Bandung Hospital was found to possess an incomplete authentication review. The hospital must improve improvements in filling out the medical resume form for authentication that has got to be filled out completely because this authentication is proof that the doctor has done treatment for his patient.